The effects of using variable lengths for degraded signal acquisition in GPS receivers - Arif Hussain; Hina Magsi; Arslan Ahmed; Hadi Hussain; Zahid Hussain Khand; Faheem Akhtar (International Journal of Electrical and Computer Engineering (IJECE), 2021)
The signal acquisition in GPS receivers is the first and very crucial process that may affect the overall performance of a navigation receiver. Acquisition program initiates a searching operation on received navigation signals to detect and identify the visible satellites. However, signal acquisition becomes a very challenging task in a degraded environment (i.e, dense urban) and the receiver may not be able to detect the satellites present in radio-vicinity, thus cannot estimate an accurate position solution. In such environments, satellite signals are attenuated and fluctuated due to fading introduced by Multipath and NLOS reception. To perform signal acquisition in such degraded environments, larger data accumulation can be effective in enhancing SNR, which tradeoff huge computational load, prolonged acquisition time and high cost of receiver. This paper highlights the effects of fading on satellite signal acquisition in GPS receiver through variable data lengths and SNR comparison, and then develops a statistical relationship between satellite visibility and SNR. Furthermore it also analyzes/investigates the tradeoff between computation load and signal data length.